2020
DOI: 10.1039/d0cp01014f
|View full text |Cite
|
Sign up to set email alerts
|

Spin-dependent Schottky barriers and vacancy-induced spin-selective ohmic contacts in magnetic vdW heterostructures

Abstract: The 2D ferromagnets, such as CrX3 (X=Cl, Br and I), have been attracting extensive attentions since they provide novel platforms to fundamental physics and device applications. Integrating CrX3 with other electrodes and substrates is an essential step to their device realization. Therefore, it is important to understand the interfacial properties between CrX3 and other 2D materials. As an illustrative example, we have investigated the heterostructures between CrX3 and graphene (CrX3/Gr) from firstprinciples. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…[25] The report shows that thicker samples with smaller work functions in graphene electrodes generally show higher TMR. Spin-dependent Schottky barrier at the CrX 3 /graphene interface has been reported in the last year by Li et al [22] These recent studies suggest that CrX 3 based compounds/heterostructures could suit spintronic applications. Therefore, it would be interesting to study the spin transport through heterojunctions consisting of CrX 3 and other interesting 2D materials, namely, the transition metal dichalcogenides (TMDC).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…[25] The report shows that thicker samples with smaller work functions in graphene electrodes generally show higher TMR. Spin-dependent Schottky barrier at the CrX 3 /graphene interface has been reported in the last year by Li et al [22] These recent studies suggest that CrX 3 based compounds/heterostructures could suit spintronic applications. Therefore, it would be interesting to study the spin transport through heterojunctions consisting of CrX 3 and other interesting 2D materials, namely, the transition metal dichalcogenides (TMDC).…”
Section: Introductionmentioning
confidence: 86%
“…These values are comparable to the previously reported CrX 3 /graphene tunneling barrier heights. [22] Although the tunneling barriers present in CrX 3 /TMDC heterostructures are independent of the electron's spin, the Schottky barrier heights are highly spin-sensitive. Therefore, these heterostructures can induce a highly spin-polarized transmission through the interface.…”
Section: Crx 3 /Tmdc Heterostructurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, heterostructures consisting of 2D ferromagnetic (FM) vdW layered materials have attracted considerable interest 8 10 . In particular, research on the 2D vdW heterobilayer composed of magnetic metals and magnetic semiconductors is still early, as it was only recently revealed that vdW monolayer (ML) or few-layer materials retain magnetism 11 13 . Furthermore, the recent discovery of novel properties of twisted vdW nonmagnetic homo and heterobilayers 14 16 further prompts the investigation of twisted vdW magnetic homo and heterobilayers.…”
Section: Introductionmentioning
confidence: 99%